Numerical Analysis of the Influence of Rectangular Deflectors and Geometry of L-Shaped Channel over the Performance of a Savonius Turbine - Andrei Luís Garcia Santos; Jaifer Corrêa Martins; Liércio André Isoldi; Gustavo da Cunha Dias; Luiz Alberto Oliveira Rocha; Jeferson Avila Souza; Elizaldo Domingues dos Santos (Journal of Marine Science and Engineering)
The present work investigates the influence of rectangular deflectors on the performance of a Savonius turbine mounted in an L-shaped channel, which represents a geometry like that found in one oscillating water column (OWC) device. It also performs a geometric investigation of the entrance region of the channel. More precisely, it investigates the effect of the height/length ratio (H1/L1) of the entering region of the channel on the system performance for three different configurations: (1) without the use of deflectors, (2) with just one deflector upstream the turbine, and (3) with one deflector upstream and another downstream the turbine. The geometric investigation is performed based on the constructal design method, and the entering channel area (A1) is the problem constraint. The performance indicators are the mechanical power in the Savonius turbine and the available power in the device. For all cases, it is considered turbulent airflow in the domain, being solved by the unsteady Reynolds Averaged Navier–Stokes mass and momentum equations. The numerical solution was obtained with the finite-volume method using the Ansys FLUENT software (version 2021 R1). The k-ω shear stress transport turbulence closure model is used. The results demonstrated that the mechanical and available powers depend on the H1/L1 ratio, regardless of the usage of deflectors. For instance, differences of up to 16.35% in mechanical power and 7.25% in available power were observed between the best and worst performance configurations in the case without deflectors. The use of deflectors resulted in increases of two and three times in available and mechanical powers, respectively, when the cases with one and two deflectors are compared with those without deflectors. This demonstrates that the enclosed domain and the insertion of the deflectors can enhance the performance of the Savonius turbine.